2013
DOI: 10.5007/2175-7925.2013v26n2p153
|View full text |Cite
|
Sign up to set email alerts
|

Morphological study of epididymides in the scorpion mud turtle in natural habitat (Kinosternon scorpioides – Linnaeus, 1976)

Abstract: ResumoEstudo morfológico dos epidídimos de jurará em habitat natural (Kinosternon scorpioides -Linnaeus, 1976). No estado do Maranhão, é encontrado o quelônio de água doce Kinosternon scorpioides, conhecido como jurará, que possui valor social, econômico e ambiental. Vinte jurarás adultos foram coletados nos meses de março, junho, setembro e dezembro, correspondendo aos dois períodos do ano: as estações chuvosa e seca. De cada animal colheram-se os epidídimos para averiguar a existência de sazonalidade reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
3
7
0
2
Order By: Relevance
“…The histological morphology of the epididymis head in T. scripta elegans, with presence of ductuli efferentes and epididymal duct interspersed with connective tissue was similar to that of other turtles (Cabral et al 2011b, Viana et al 2013, Olukole et al 2014. The ductuli efferentes are responsible for the transport of spermatozoa from the testis to the epididymis, and present epithelium capable of reabsorbing more than 90% of the luminal fluid, increasing the concentration of spermatozoa entering the epididymis (Hansen et al 2004).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The histological morphology of the epididymis head in T. scripta elegans, with presence of ductuli efferentes and epididymal duct interspersed with connective tissue was similar to that of other turtles (Cabral et al 2011b, Viana et al 2013, Olukole et al 2014. The ductuli efferentes are responsible for the transport of spermatozoa from the testis to the epididymis, and present epithelium capable of reabsorbing more than 90% of the luminal fluid, increasing the concentration of spermatozoa entering the epididymis (Hansen et al 2004).…”
Section: Discussionsupporting
confidence: 60%
“…The ductuli efferentes are responsible for the transport of spermatozoa from the testis to the epididymis, and present epithelium capable of reabsorbing more than 90% of the luminal fluid, increasing the concentration of spermatozoa entering the epididymis (Hansen et al 2004). In T. scripta elegans, groups of three to 10 ductuli efferentes were observed, as in hamsters (3-10; Ford Junior et al 2014), mammals (5-10; Acharya et al 2015), and Pelusios castaneus (5-8;Olukole et al 2014), whereas the observed simple columnar epithelium differed from the pseudostratified columnar epithelium with areas of ciliated and non-ciliated cells in P. geoffroanus (Cabral et al 2011b); of the simple cuboidal epithelium in K. scorpioides (Viana et al 2013), and of the pseudostratified columnar epithelium in Pelusios castaneus (Olukole et al 2014). In contrast, presence of smooth muscle tissue and loose connective tissue surrounding the ductuli efferentes, irregular contour, and empty lumen were also observed in these species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vas deferens in jurará are a pair of simple structures, with a convoluted path that extends from the epididymis (Viana 2013) to the cloaca, with the function of transporting and storing spermatozoids. The penis, in turn, is grooved, and composed by the root, body and gland, located in the ventral floor of the cloaca, in which it attaches via a retractor muscle, and is protected by the foreskin (Carvalho et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Foram utilizados 06 exemplares de muçuã adultos de cativeiro em jejum, sendo três machos e três fêmeas. Para eutanásia, foi utilizado o Tiopental sódico 2,5% por via intramuscular conforme protocolo (8)(9)(10)(11) . Os cortes das três regiões do estômago foram submetidos à técnica da estreptovidina-peroxidase para detecção de antígenos de enteroglucagon presente no epitélio e glândulas do estômago do muçuã.…”
Section: Methodsunclassified